Adoption of Sustainable Agriculture Intensification in Maize-Based Farming Systems of Katete District in Zambia - Hamazakaza, Petan; Kabwe, Gillian; Kuntashula, Elias; Egeru, Anthony; Asiimwe, Robert (Land, 2022)
Sustainable agricultural intensification (SAI) has been hailed as the solution to increasing crop productivity among farmers. Despite the significant promotion, there still remains a dearth of information on the adoption and intensity of SAI in Zambia. This study sought to identify factors that influence farmers’ adoption of SAI practices and intensity of use. A cross-sectional survey was conducted among 300 smallholder farmers of Katete district in Zambia. The Cragg’s double hurdle model was used to assess the key decision factors for SAI adoption and intensity of use. Empirical estimates revealed that limited years of farming and smaller total cropped field size were statistically significant decision factors that led to a reduced likelihood of SAI adoption. The results of the truncated model showed that smaller farm sizes and limited access to farmer extension services reduced the adoption intensity of SAI practices, whereas farmer affiliation with farmer associations and farmer training in crop production increased SAI adoption intensity. We recommend an increase in farmer training on and sensitization to the benefits of SAI practices aligned to their respective landholdings.
Keywords: Sustainable agriculture intensification; Adoption; Double hurdle